INDICATORS NT-PROBNP and ST-2 IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH ST-SEGMENT ELEVATION - E. V. Khorolets; L. A. Khaisheva; S. V. Shlyk (Атеросклероз, 2017)
The goal was to study clinical features, NTproBNP and ST-2 indices in patients with acute myocardial infarction with ST segment elevation (STEMI) complicated by heart failure. Materials and methods. Included 150 patients with STEMI in the first 24 hours from the onset of the disease, with arterial hypertension, acute heart failure (AHF), Killip I-IV degree. All patients underwent clinical, laboratory and instrumental examinations: on admission to the hospital (first visit) and discharge (second visit). Results. The average age of the patients was 61.70 ± 2.96 years. In the dynamics of treatment of STEMI patients in the general group, a decrease in the level of ST-2 was observed against a background of high concentration of NTproBNP. With the progression of the degree of AHF Killip II-IV, the level of ST-2 and NTproBNP increases. At the first visit in the ST-2 ≥ 35 ng/mL group, the ST-2 and NTproBNP levels were statistically higher than those in the ST-2 group <35 ng/ml. At the second visit in ST-2 ≥ 35 ng/ml group, ST-2 level was decreased, and NTproBNP values remained high in the studied groups. A statistically significant reduction in the ejection fraction in patients with ST-2 ≥ 35 ng/ml was found to be statistically significant compared to the ST-2 group <35 ng/ml. The conclusion. In STEMI patients, ST-2 and NTproBNP are prognostic markers for the progression of acute heart failure. In the dynamics of inpatient treatment, the level of ST-2 persisted more than 35 ng/ml, in the ST-2 group of 35 ng/ml has the most unfavorable prognosis of heart failure.